Bilateral Increase of Matrix Metalloproteinase-9 Expression in Tears After the Unilateral Decrease of Corneal Sensitivity - Lee, Seung Hyeun; Chun, Yeoun Sook; Moon, Nam Ju; Kim, Kyoung Woo (Cornea, 2022)
The purpose of this study is to analyze bilateral changes of matrix metalloproteinase-9 (MMP-9) expression in the tear film in patients with unilateral neurotrophic keratitis. We included 24 eyes from 24 subjects with normal corneal sensitivity according to Cochet-Bonnet corneal esthesiometry in the control group and 25 subjects with the unilateral neurotrophic keratitis in the unilateral decrease of corneal sensitivity (UDCS) group. The expression of MMP-9 in tears was assessed using point-of-care immunoassay. The clinical parameters including meibomian gland plugging, quality of the secreted meibum, tear secretion using Schirmer I without anesthesia, and corneal erosions were evaluated among the control, affected, and contralateral unaffected eyes in the UDCS group. Tear MMP-9 grades in affected (2.5 ± 1.0) and contralateral eyes (2.6 ± 0.9) in the UDCS group were higher than those in control eyes (1.5 ± 0.7, P = 0.0003 and P = 0.0006, respectively). The lacrimal secretion decreased in the affected eyes but preserved in the contralateral eyes. There was no difference in corneal erosion scores between control eyes and contralateral eyes in the UDCS group. Tear MMP-9 grades in the contralateral eyes were significantly correlated with the meibum quality grades in the contralateral eyes (r = 0.525 and P = 0.025). Patients with the unilateral neurotrophic keratitis demonstrated a significant bilateral increase of the MMP-9 expression in the tear film as compared with controls. Despite the tearing reflex and corneal surface barrier being preserved in the unaffected contralateral eyes, it is necessary to pay attention to the possible attenuation of meibomian gland function in the opposite eyes as well.